MFAP4 Promotes Vascular Smooth Muscle Migration, Proliferation and Accelerates Neointima Formation. Issue 1 (January 2016) - Schlosser, Anders; Pilecki, Bartosz; Hemstra, Line E.; Kejling, Karin; Kristmannsdottir, Gudlaug B.; Wulf-Johansson, Helle; Moeller, Jesper B.; Füchtbauer, Ernst-Martin; Nielsen, Ole; Kirketerp-Møller, Katrine; Dubey, Lalit K.; Hansen, Pernille B.L.; et al.
Abstract : Objective—: Arterial injury stimulates remodeling responses that, when excessive, lead to stenosis. These responses are influenced by integrin signaling in vascular smooth muscle cells (VSMCs). Microfibrillar-associated protein 4 (MFAP4) is an integrin ligand localized to extracellular matrix fibers in the vascular wall. The role of MFAP4 in vascular biology is unknown. We aimed to test the hypothesis that MFAP4 would enhance integrin-dependent VSMC activation. Approach and Results—: We produced Mfap4 -deficient ( Mfap4 −/− ) mice and performed carotid artery ligation to explore the role of MFAP4 in vascular biology in vivo. Furthermore, we investigated the effects of MFAP4 in neointimal formation ex vivo and in primary VSMC and monocyte cultures in vitro. When challenged with carotid artery ligation, Mfap4 −/− mice exhibited delayed neointimal formation, accompanied by early reduction in the number of proliferating medial and neointimal cells, as well as infiltrating leukocytes. Delayed neointimal formation was associated with decreased cross-sectional area of ligated Mfap4 −/− carotid arteries resulting in lumen narrowing 28 days after ligation. MFAP4 blockade prohibited the formation of neointimal hyperplasia ex vivo. Moreover, we demonstrated that MFAP4 is a ligand for integrin αV β3 and mediates VSMC phosphorylation of focal adhesion kinase, migration, and proliferation in vitro. MFAP4-dependent VSMC activation was reversible by treatment with MFAP4-blocking antibodies and inhibitors of focal adhesion kinase and downstream kinases. In addition, we showed that MFAP4 promotes monocyte chemotaxis in integrin αV β3 –dependent manner. Conclusions—: MFAP4 regulates integrin αV β3 –induced VSMC proliferation and migration, as well as monocyte chemotaxis, and accelerates neointimal hyperplasia after vascular injury. Abstract : Supplemental Digital Content is available in the text.